Pioneers of Zionism: Hess, Pinsker, Rülf Messianism, Settlement Policy, and the Israeli-Palestinian Conflict - Schoeps, Julius H. (2013)
The emerging Jewish national consciousness in Europe toward the end of the 19th century claims many spiritual fathers, some of which have been seriously underestimated so far. Zionist intellectuals such as Moses Hess, Leon Pinsker and Isaac Rülf were already committed to the self-liberation of the Jewish people long before Theodor Herzl. Their experiences and observations brought them to believe that the emancipation and integration of Jews were not realistically possible in Europe. Instead, they began to think in national and territorial terms. The author explores the question as to what extent religious messianism influenced the ideas of these men and how this reflects in today's collective Israeli consciousness. In a comprehensive epilogue, Julius H. Schoeps critically correlates ideas of messianic salvation, Zionist pioneer ideals, the settler's movement before and after 1967, and the unsolved conflict between Israelis and Palestinians which has been lasting for over 100 years...